Epigenetics and the Developmental Origins of Health and Disease: Parental environment signalling to the epigenome, critical time windows and sculpting the adult phenotype. (January 2020) - Safi-Stibler, Sofiane; Gabory, Anne
Abstract: The literature about Developmental Origins of Health and Disease (DOHaD) studies is considerably growing. Maternal and paternal environment, during all the development of the individual from gametogenesis to weaning and beyond, as well as the psychosocial environment in childhood and teenage, can shape the adult and the elderly person's susceptibility to her/his own environment and diseases. This non-conventional, non-genetic, inheritance is underlain by several mechanisms among which epigenetics is obviously central, due to the notion of memory of early decisional events during development even when this stimulus is gone, that is implied in Waddington's developmental concept. This review first summarizes the different mechanisms by which the environment can model the epigenome: receptor signalling, energy metabolism and signal mechanotransduction from extracellular matrix to chromatin. Then an overview of the epigenetic changes in response to maternal environment during the vulnerability time windows, gametogenesis, early development, placentation and foetal growth, and postnatal period, is described, with the specific example of overnutrition and food deprivation. The implication of epigenetics in DOHaD is obvious, however the precise causal chain from early environment to the epigenome modifications to the phenotype still needs to be deciphered.